Significance and Impact of the Intersphincteric Plane Sepsis in the Management of the Perianal Sepsis: Ultrasound Study - Youssef, Ashraf Talaat (Journal of Gastrointestinal and Abdominal Radiology, 2021)
Background The intersphincteric plane (ISP) is a potential space between the external and the internal anal sphincters. About 90% of the perianal sepsis is caused by an obstruction of the ducts of anal glands with subsequent secondary bacterial infection. The imaging modalities used to diagnose perianal sepsis are the ultrasound via endoanal and transperineal routes and magnetic resonance imaging.Objective  The study aimed to identify the various patterns of the ISP sepsis and their incidence among our study group and to clarify the significance of ISP in the pathogenesis of anorectal abscesses and various types of perianal fistula tracts, to optimize the surgical management.Methods Retrospective descriptive study in which 57 patients with an ISP sepsis were evaluated with full medical history, clinical exam, and ultrasound; the final diagnosis was based on combining the results of ultrasound, digital rectal examination under anesthesia, and the operative results.Results The current study showed many patterns of the ISP sepsis and estimated the incidence of each pattern among our study group; such patterns could be fistula tracts, sinus tracts, abscesses, intersphincteric abscess with supralevator extension, sinus with abscess formation, fistula with abscess formation, distension of the ISP with free pus, and other complex patterns like horse abscess, abscess with transsphincteric sinus, and ISP fistula/sinus with transsphincteric branches.Conclusion Understanding the role of the ISP in the pathogenesis of anorectal abscesses and perianal fistula tracts can help in reaching the optimum way of management.
Keywords: intersphincteric plane sepsis; management of perianal fistula; anorectal abscess; pathogenesis of perianal fistula; transperineal ultrasound